Optimization of Window Study Endpoints in Endometrial Cancer - Kitson, Sarah J.; Maskell, Zoe; Sivalingam, Vanitha N.; Shaw, Joseph; Crosbie, Emma J. (Frontiers in Oncology, 2019)
Pre-surgical window studies rely on the accurate quantification of biomarkers as surrogates of disease response. In endometrial cancer, this has traditionally involved comparing immunohistochemical expression in diagnostic endometrial biopsies with the post-treatment hysterectomy specimen. This strategy is at risk of generating erroneous results if significant hypoxia occurs during surgery or delays in fixation of tissues lead to protein loss. Immunohistochemical expression of commonly studied biomarkers in window studies were compared in pre-operative endometrial biopsies and hysterectomy specimens taken on the same day from 75 women with endometrial cancer enrolled in a clinical trial. Differences in expression were correlated with clinico-pathological variables and tissue handling. Expression of Ki-67, markers of the PI3K-Akt-mTOR and insulin signaling pathways and hormone receptors was significantly lower in the hysterectomy specimen than the corresponding endometrial biopsy (all p<0.0001). In contrast, expression of the cancer stem cell markers, CD133 and ALDH, were similar in the two specimens. The extent to which protein expression was lost in the hysterectomy specimen was closely correlated with baseline expression in the endometrial biopsy (all p≤0.001). Bisection of the uterus prior to placement in formalin partially preserved protein expression suggesting prompt fixation is critical. These results call into question findings from earlier endometrial cancer window studies which have relied on the hysterectomy specimen for analysis and suggest a post-intervention endometrial biopsy should be included in trials going forward.